Heterogeneity of CD40 Expression in Different Types of High-Risk Endometrial Cancer Affects Discordant Prognostic Outcomes - Zhao N; Sun B; Cheng Y; Wang J (Dove Medical Press, 2023)
Na Zhao,1,2,* Bowen Sun,1,* Yuan Cheng,1 Jianliu Wang1 1Department of Gynecology and Obstetrics, Peking University People's Hospital, Beijing, 100044, People's Republic of China; 2Department of Obstetrics and Gynecology, Peking University International Hospital, Beijng, 102206, People's Republic of China*These authors contributed equally to this workCorrespondence: Jianliu Wang; Yuan Cheng, Department of Gynecology and Obstetrics, Peking University People's Hospital, Beijing, 100044, People's Republic of China, Tel +86-10-88324385 ; +86-10-88324474, Email wangjianliu1203@163.com; chengyuan@bjmu.edu.cnBackground: The role of immune checkpoint inhibitors in endometrial cancer is limited. At present, the anti-programmed cell death protein 1 (anti-PD-1) antibody is only used in patients with recurrence or metastasis. CD40 is an important immune checkpoint, which is expressed in tumor cells and immune cells, but its distribution characteristics in endometrial carcinoma have not been explored.Methods: Sixty-eight cases of primary endometrial carcinoma treated in Peking University People's Hospital from January 2010 to December 2020 were collected, including 28 cases of poorly differentiated endometrioid adenocarcinoma, 23 cases of serous carcinoma and 17 cases of clear cell carcinoma. The relationship of CD40 expression and PD-L1 expression with their prognosis was analyzed by immunohistochemistry.Results: We found that CD40 had higher expression in non-endometrioid endometrial carcinoma, which lead to the worse prognosis. The effect of high expression of CD40 on the prognosis of endometrioid adenocarcinoma was not significantly different, and most patients with good prognosis. We found that the proportion of CD40 distribution in tumor cells and immune cells may be associated with this heterogeneity.Conclusion: The expression of CD40 in different endometrial cancers may indicate the difference prognosis, which may become a potential target for drug treatment of non-endometrioid endometrial carcinoma.Keywords: endometrial cancer, CD40, PD-L1, heterogeneity, immune checkpoint